How Effective are Matching Schemes in Enticing Low-income Earners to Save More for Retirement? Evidence from a National Scheme - Marc K. Chan; Cain Polidano; Ha Vu; Roger Wilkins; Andrew Carter; Hang To (Institute of Labor Economics (IZA), 2020)
Concerns over the adequacy of low and middle-income earner contributions to retirement plans have led governments to introduce targeted matching schemes. In this study, we examine the effects of a simple and generous Australian scheme using administrative tax-filer data, exploiting longitudinal changes in eligibility and match rates. We find small increases in the proportion who contribute and bunching at the eligible maximum, but lower average contributions because the matching payment displaces contributions of high contributors. Contributions through unmatched channels are also crowded out. These findings highlight the difficulties of targeting matching schemes and question the merits of simplifying them.
Keywords: I3; J14; H55; 330; private pension; matching schemes; retirement income; aging population